THE SECURITY OF LOCAL FOOD AND DIVERSIFYING COMMUNITY CONSUMPTION (Study on Waimangit Village Community of Buru Island) - Umanailo, M. Chairul Basrun (SOCA: Jurnal Sosial Ekonomi Pertanian, 2018)
This research has been conducted in Waimangit village of Buru Island with an effort to Analyze community food security planning as well as make projections for diversification of consumption and local food security of the community. The approach used is qualitative with the basic method of descriptive analysis. In this study, the description of local people's food consumption is still low with the level of diversification of food consumption which is still relatively low then there are also factors that greatly affect the level of diversification of food consumption such as processing expertise, the number of household members and the knowledge of the community itself, then there has been no shift of rice consumption pattern to local food, local food consumption condition only happened at certain age segment with very limited amount and finally food security level for Waimangit Village community is generally vulnerable, where average household of farmer based ladder long term that makes rice consumption a consumptive need.